Contact Deformation Behavior of an Elastic Silicone/SiC Abrasive in Grinding and Polishing - Li, N.; Ding, J.F.; Xuan, Z.Y.; Huang, J.M.; Lin, Z.P. (Проблемы прочности, 2018)
An elastic abrasive of the new type having the advantage of effectively controlled contact pressure and uniform deformation was developed. It provides complete lamination of the surface, effective treatment of the curved mold cavity, as well as improves the processing efficiency. It permits of fine cavity surface finishing.